An Analysis of Air Pollution Emission from Semi-Trailer Truck Transportation in Laem Chabang Municipality: A Structural Equation Modeling - Senarak, Chalermpong (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 4 (2019): October-December 2019, 2019)
The demand growth for container shipping in most countries increases the number of semi-trailer truck on the roads in port-proximate communities; consequently, the residents inevitably experience with air pollution and other externalities from STT transportation than ever. While a clear-cut solution has not been identified in theory, the current study attempted to narrow this gap by developing a holistic model focusing on all fundamental elements. To formulate the model, the relevant attributions were developed based on a literature review and used to develop a questionnaire survey randomly distributed to the respondents in the five communities in Laem Chabang municipality. Based on 414 responses, the structural equation modeling was adopted to analyze the relationships among 13 endogenous variables and 15 exogenous variables which were conceptualized based on the existing theories, and thereinafter adjusted based on the modification indices. The findings demonstrated that the STTs’ safety standard had a greater impact on air pollution than that of STT drivers’ behaviors, while road accidents and traffic congestion played an important role as an intermediary passing an indirect effect from its origins to air pollution emission. Therefore, the best solution was to eliminate the original sources of air pollution, but eradicating its intermediate sources would also help address the poor local air quality. Keywords: Air Pollution Emission, Semi-Trailer Truck, Transportation, Laem Chabang Municipality, Structural Equation     Modeling